Patients with laboratory evidence of West Nile virus disease without reported fever. (2019) - Landry, K.; Rabe, I. B.; Messenger, S. L.; Hacker, J. K.; Salas, M. L.; Scott-Waldron, C.; Haydel, D.; Rider, E.; Simonson, S.; Brown, C. M.; Smole, S. C.; Neitzel, D. F.; et al.
Abstract: In 2013, the national surveillance case definition for West Nile virus (WNV) disease was revised to remove fever as a criterion for neuroinvasive disease and require at most subjective fever for non-neuroinvasive disease. The aims of this project were to determine how often afebrile WNV disease occurs and assess differences among patients with and without fever. We included cases with laboratory evidence of WNV disease reported from four states in 2014. We compared demographics, clinical symptoms and laboratory evidence for patients with and without fever and stratified the analysis by neuroinvasive and non-neuroinvasive presentations. Among 956 included patients, 39 (4%) had no fever; this proportion was similar among patients with and without neuroinvasive disease symptoms. For neuroinvasive and non-neuroinvasive patients, there were no differences in age, sex, or laboratory evidence between febrile and afebrile patients, but hospitalisations were more common among patients with fever ( P < 0.01). The only significant difference in symptoms was for ataxia, which was more common in neuroinvasive patients without fever ( P = 0.04). Only 5% of non-neuroinvasive patients did not meet the WNV case definition due to lack of fever. The evidence presented here supports the changes made to the national case definition in 2013.